Penerapan Bimbingan Konseling terhadap Siswa Introvert di Sekolah Dasar - Zuhdi, Setia Hasanah; Perdana, Parrisca Indra (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
The problem in this study is how individual counseling works to change introverted behavior in elementary school students. This study uses a qualitative research model by conducting observations and interviews with the aim of improving students’ social skills so that they can further develop their quality and develop their competencies optimally. This counseling guidance is carried out by approaching students so that they can teach them good social skills, namely being able to communicate and increase students’ self-confidence. The results of the study indicate that the application of individual counseling services provided to students is very good and the implementation of counseling services shown is by changes in student behavior from being introverted to being lowly introverted.